Corrosion in the military II - Agarwala, Vinod S. (Trans Tech Publications, 2008)
This special collection deals with the escalating cost of corrosion. The realization that corrosion has an enormous impact upon the world economy, human factors and the global environment makes governments, industries and private institutions first give serious consideration to corrosion before investing in any new acquisition. The collection is divided into: Section I: Coatings / Corrosion Inhibitors; Section II: Corrosion Prevention Control; Section III: Monitoring and Diagnostics; Section IV: Management and Data Analysis; Section V: Corrosion Mechanism / MIC; Section VI: Stress Induced Cracking; Section VII: Metal Joining Concepts. The up-to-date knowledge gathered from internationally known scientists, academicians, planning and practising engineers, program managers and technicians makes this collection an invaluable and informative educational work. The pooling and leveraging of each others' knowledge, experience, expertise and talents at the global scale proves to be most meaningful, beneficial and productive. It further helps to propel corrosion research into the next level of technological advancement.
Keywords: Corrosion and anti-corrosives -- Military aspects -- Congresses.; elektronické knihy; electronic books